Endnu en gang: om at fortælle - Hamburger, Käte (K&K - Kultur og Klasse, 2006)
Forsøg på et svar og en afklaring Once again: About Narration In 1957 the German literary scholar Käte Hamburger published an original and controversial book on the language of literary fiction (Die Logik der Dichtung, English translation The Logic of Literature (1973)). According to Hamburger the constitutive mark of epic fiction (the third-person form of narration) is that it represents human subjectivity in a manner that has no counterpart in ordinary life. Furthermore this »logic of literature« is not a matter of interpretation or stylistics, but is based on fundamental and distinguishable linguistic features, e.g. the loss of the sense of »pastness« in the praeterite tense. Hamburger’s book raised a lot of debate and objections, and in 1965 she summarized the discussion and gave her reply in the article »Noch einmal: Vom Erzählen« (Once again: About Narration), translated into Danish for this issue of K&K. The crucial elements of tense in the novel, the role of the narrator and the art of fiction are once again investigated by Hamburger in this final contribution.